Cantando a gente brinca, brincando a gente aprende - Hortêncio, Claudomiro Braga; Carvalho, Elza Dias de Oliveira; Beraldo, Marciene Borges; Silva, Noemia de Sena Rosa; Botassim, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf